Դռնփակ պատարագի ավանդույթը Հայ Առաքելական Եկեղեցու ծիսակարգում - Ղազարյան, Գևորգ (Մատենադարան)
In 2020–2021, due to the spread of the COVID-19 pandemic, the entire Christian world began to conduct public worship behind closed doors. For the Armenian Apostolic Church this practice was not unprecedented because in the Middle Ages the Divine Liturgy behind closed doors was one of the most characteristic features of the Armenian rite. The origins of this remarkable phenomenon date back to the 8th-9th centuries, when funeral services in monasteries were conducted privately, without public participation. On the other hand, Lent, with its strict and restrictive instructions, seems to have contributed to the formation of this practice. Closed-door Divine Liturgy became widespread in the Bagratid and later in the Zak‘arid periods of Armenian history, almost entirely replacing the celebration of the Bloodless Sacrifice with the entire clergy and people. This deviation was sharply criticized not only by the Byzantines, Latins and Syrians but also by local clerics and theologians such as Nersēs Lambronats‘i and Simeon Pghndzahanets‘i. This restricted the use of closed doors during the liturgy to the period of Great Lent in the 14th century, and four centuries later a radical change in the rite was introduced: while previously the doors were locked and the people assembled in the gavit‘ (narthex) during the whole Great Lent, from the 18th century onwards the Liturgy has been celebrated in the altar closed by a veil and the people gathering in the church but without the right to approach the Holy Communion, except for the feasts of the Purification, Annunciation, Entrance of St. Gregory the Illuminator into the Pit (the 6th Saturday in Lent), Palm Sunday and Holy Thursday. В 2020–2021 гг. из-за пандемии COVID-19 весь христианский мир стал совершать богослужения при закрытых дверях. Для Армянской Апостольской Церкви данная практика не беспрецедентна, так как в Средневековье Литургия при закрытых дверях была одной из самых характерных особенностей армянского обряда. Корни этого примечательного феномена восходят к VIII–IX в., когда заупокойные Литургии в монастырях служили в частном порядке, без участия народа. В формирование этой практики, по-видимому, внес свой вклад и Великий Пост с его строгими ограничительными предписаниями. Литургия при закрытых дверях получила широкое распространение в Багратидский и, далее, в Захаридский периоды армянской истории, почти целиком вытеснив совершение Бескровной Жертвы с участием всего духовенства и народа. Это отклонение стало предметом острой критики не только со стороны византийцев, латинян и сирийцев, но и отечественных церковных мужей и богословов – таких, как Нерсес Ламбронаци и Симеон Пхиндзаханеци. Благодаря этому, к XIV в. практика совершения Литургии при закрытых дверях была ограничена лишь периодом Великого Поста, а через четыре столетия была внесена серъезная поправка и в сам чин: если ранее на всю Четыредесятницу запирались двери церкви, а народ собирался в гавите (притворе), то с XVIII в. Литургия совершается в закрытом катапетазмой (завесой) алтаре, а народ находится в самом храме – впрочем, без права приступать к Чаше, за исключением праздников Сретения, Благовещения, Мук и Ввержения св. Григория Просветителя в ров (6-ая суббота Поста), Вербного воскресения и Великого Четверга.
Keywords: Հայոց ծիսակարգ